Advance Technologies and Problems in Halal & none-Halal Food's Detection - Mirghani, Mohamed Elwathig Saeed (2009)
Halal is an Islamic term for permissible, it comes from the holy Quraan and the traditions of our beloved Prophet Mohammad (Peace be upon Him) who showed us the distinction between halal and non-halal. An example from Quraan is “O ye people! Eat of what is on earth, Halal and good; and do not follow the footsteps of the Evil One, for he is to you an avowed enemy.” (Albaqarah; Verse 168). Other examples are “He has only forbidden you dead meat, and blood, and the flesh of swine and that on which any other name hath been invoked besides that of Allah. But if one is forced by necessity, without willful disobedience, nor transgressing due limits, - then is he guiltless. For Allah is oft-forgiving, most merciful.” (Surah 2; Verse 173) and “O ye who believe! Forbid not the good thing which Allah hath made Halal for you, and transgress not. Lo Allah loveth not transgressors. Eat of that which Allah hath bestowed on you as food Halal and Good, and keep your duty to Allah in Whom ye are believers.”(Al-Maidah; Verses 87, 88). There are also so many Hadith by Prophet Mohammad (Peace be upon Him) regarding halal, non-halal and haram. Ensuring food and other consumer products authentically halal is obligatory for every Muslims. Halal should involve approval of all ingredients and all food processing at any stage of the production – from farm to fork concept. Bearing in mind that Muslim population is about two billion worldwide; many companies are looking at halal concept as a new tool for marketing. It is also very important to know that in Islam, food should be Halal and Taiyib (good) as mentioned in many Quraanic verses. Halal food means that it ensures high quality and safety conforming international standards such as food safety according to Hazard Analysis and Critical Control Point (HACCP) and of course it should be permitted under the Islamic Shariah law. It is very challenging and increasingly difficult for Muslims to ensure halal status of food in the market due to the diversification of sources acquired globally for food processing and production. This trend has raised concerns among Muslim consumers regarding processed food. Adulteration of value-added food products - involving the replacement of high cost ingredients with lower grade and cheaper substitutes can be very attractive and lucrative for food manufacturers or raw material suppliers. Many fraudulent and deception cases reported worldwide involving adulteration of haram ingredients in halal food (especially porcine-based products).